1970
DOI: 10.1128/jb.101.1.196-201.1970
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Exosporium from Spores of Bacillus cereus

Abstract: Homogeneous fragments of exosporium were extricated in centigram amounts from dormant spores of Bacillus cereus and analyzed for intrinsic constituents. The membrane proved to be chemically complex but not unique, consisting mainly of protein (52%), amino and neutral polysaccharides (20%), lipids (18%), and ash (4%). Seventeen common amino acids were identified by chromatography, and were present in usual proportions except for low levels of cystine-cysteine, methionine, tyrosine, and histidine. Glucosamine wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 32 publications
4
58
0
Order By: Relevance
“…The paracrystalline layer has a hexagonal, perforate lattice structure (Beaman et al 1971). In addition to protein components, the native exosporium fraction contained lipid and carbohydrate (Matz et al 1970;Beaman et al 1971). Approximately eight protein components were reported to be present in the exosporium, but these were not characterized further (Beaman et al 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The paracrystalline layer has a hexagonal, perforate lattice structure (Beaman et al 1971). In addition to protein components, the native exosporium fraction contained lipid and carbohydrate (Matz et al 1970;Beaman et al 1971). Approximately eight protein components were reported to be present in the exosporium, but these were not characterized further (Beaman et al 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The IEP of carboxylic acids associated with protein is between 4 and 5 while the IEP of carboxylic acid associated with polysaccharides are closer to 3. Previous studies have also reported that the surfaces of spores consist largely of protein and polysaccharide (Matz et al 1970), while the spore cortex (mid section of the spore) consists of peptidoglycan. The diffusion of protons into deeper compartments can affect zeta potentials of individual spores depending on the electro-osmotic fluid flow through these layers (Poortinga et al 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, there has been a shift in focus to the characterization of surface chemical composition of intact spores aimed at the development of rapid methods for detecting spores of pathological importance such as Bacillus anthracis and Bacillus cereus (Fox et al 2003). The outermost layer of these bacillus species has an exosporium comprised of glycoproteins and lipids (Gerhardt and Ribi 1964;Matz et al 1970;Redmond et al 2004). However, some spores of thermophilic bacilli isolated from hot springs have an additional protective coat (Panessa-Warren et al 2007).…”
mentioning
confidence: 99%
“…Neutral sugars could not be detected. In contrast, the exosporium of B. cereus contained two neutral sugars, glucose and rhamnose (20). Total lipids, estimated as dry weight, amounted to 13.8%, but detailed lipid analysis has not yet been carried out.…”
Section: Chemical Composition Of Purified Exosporium Fragmentsmentioning
confidence: 99%
“…The exosporia of Bacillus cereus (7,20) and Bacillus thuringiensis (25) were isolated from spores and examined in detail concerning their chemical composition. In contrast, little information on the morphological and chemical properties of exosporia from the genus Clostridium is available.…”
mentioning
confidence: 99%